Tweaking the Human Circadian Clock with Light - Oren, Dan A.; Terman, Michael (Science (American Association for the Advancement of Science), 1998)
Scientists show that the endogenous clock of humans can be entrained by light application to an unexpected spot, the popliteal region--the back of the knee. Results show that popliteal illumination with a visible-spectrum light source can shift human circadian rhythms without any transduction of light through the eye.